TEMPORAL VARIATION OF GROUNDWATER QUALITY IN SLEMAN, YOGYAKARTA, INDONESIA - Yureana Wijayanti; Markus Fittkow; Riana Ayu Kusumadewi; Oki Setyandito (Universitas Trisakti, 2021)
Groundwater quality evaluation is important to gain an insight of contamination source. It can later be utilized to review the implementation of a water resource management policy in a specific region. Aim: This study evaluate the short-term temporal variation of groundwater quality and its possible contamination source in Sleman, Yogyakarta. Methodology and Results: the statistical approach was utilized using boxplot, principle component analysis (PCA) and correlation matrices, to the data for 50 sampling sites. The data of groundwater quality are available from the local environmental authority of Environmental Agency Sleman.The box plots revealed that groundwater quality might largely influenced by rainfall in the area. The factor loading of PCA presented that the ratio of concentration of both chloride and TDS are the most varied of all samples, and the less variable parameter is fluoride. The pair of groundwater quality parameter which had strong correlation were varied in each year, except for TDS and chloride that showed strong correlation in all three years. Nitrite had strong correlation with iron in 2017 and, nitrite also had strong correlation with both manganese and fluoride in 2019. The existence of fluoride in correlation with other parameter might give an insight of contamination from livestock wastes, where in the study area there are many poultry and cow farms, and small scale chicken slaughter industries. Conclusion, significant and impact study: This study gives preliminary understanding on temporal variation of groundwater quality, for further research on groundwater quality in Sleman, Yogyakarta.